THE ANTIBACTERIAL EFFECT OF URENA LOBATA L. FROMV GUANGXI ON MICE WITH STAPHYLOCOCCUS AUREUS PNEUMONIA - Yang, Yufang; Huang, Zhenguang; Zou, Xiaoqin; Zhong, Xiaobin; Liang, Xueyan; Zhou, Jinling (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Alcohol extract from the root of Urena lobata L. (ULL) had broad spectrum antimicrobial activity.Studies in vitro have sho that ULL aqueous extract has antibacterial effect on S. aureusis, and the combination therapyof the ULL aqueous extract with cefazolin sodium showed additive effect.Materials and Methods: The mice underwent nasal inhalation with S. aureus, a subset of mice were intra-gastricgavage with ULL and/or intravenous injection cefazolin sodium twice daily. After being exposed to S. aureus for 5days, 10 days and 14 days respectively, the white blood cells count (WBC), neutrophils absolute value (NEU) and theneutrophil percentage (NEU%) in peripheral blood, as well as the levels of serum immunoglobulin (Ig) G and IgMwere determined using commercial kits. The colony count of S. aureus, the levels of interleukin (IL) -6 and IL-10 ofmice lung tissue were detected, and the pathological changes of lung tissue were examined using H & E staining.Results: ULL significantly protected against S. aureus pneumonia, as evidenced by the remarkable decrease in therate of S. aureus colony count/lung weight, WBC, NEU and NEU% in peripheral blood, as well as the attenuation oflung histopathological damage. Additionally, ULL+cefazolin could have markedly reduced the rate of S. aureuscolony count/lung weight when compared with cefazolin. Furthermore, ULL and ULL+cefazolin both couldsignificantly decrease the serum levels of IgG and IgM, and the levels of IL-6, IL-10 in mice lung tissue.Conclusion: This study first demonstrated that ULL may have potential use as a therapeutic agent for S. aureuspneumonia, and the roles of IgG, IgM, IL-6 and IL-10 in ULL protection against S. aureus pneumonia remain to befurther studied.